Three Types of IS-A Statement in Diagnostic Classifications: Three Types of Knowledge Needed for Development and Maintenance - Flier, F. J.; de Vries Robbé, P. F.; Zanstra, P. E. (Methods of Information in Medicine, 1998)
Update mechanisms for diagnostic classifications should capture changes in medical knowledge but also allow for comparability across versions. This paper provides a basis for such a mechanism by describing types of IS-A statement and types of knowledge used in the construction of diagnostic classifications. Three types of IS-A statement are used: ‘A is by definition a 8’, ‘A is probably a 8’ and ‘A is in theory necessarily a 8’. Each relates to a different type of knowedge: knowledge of linguistic conventions, of probabilities, and of empirical theories and their status, respectively. Consequently, the development and maintenance of diagnostic classifications requires a collaboration of medical terminologists and medical scientists. The role of the latter is especially important during updating. Updating is necessitated by changing probabilities and by the introduction or changing status of empirical theories. The linguistic notion of hyponymy oversimplifies the issue.
Keywords: Classificaton; Terminology; Semantics; Logic; Knowledge Representation